Psicanálise e saúde mental: uma análise através da clínica com crianças - Travaglia, Aline Alves da Silva (2014)
Within the topic of mental health and the field of psychoanalysis, we shall think about the children s assistance and the position of the analyst, with that practice as inserted in the institutional environment. Taking as a ground the method of clinical vignettes, we will use some clinical cases as markers to put in question the position of the psychoanalyst s position before the child's suffering. It is mandatory the understanding of some clinical tools as well as their expansion to the analyst s political job, in public and institutional spaces, it is necessary to furnish the idea of an ethical and political listening. We proceed then criticizing the hegemonic understanding of mental healthcare and their references in contemporary psychopathology, in order to understand the addressing of the subjects using the medical speech to prompt care via mental health institutions. Charting a critique of contemporary psychopathology, we intend to comprehend how the symptoms becomes something difficult to be evaluated when the suffering is obturated into diagnostic nomenclatures, but instead, the work of the analyst appears as a hearing that raises the subject to put himself in his uniqueness. To welcome the complaint referred to the medical and psychiatric field and to put ahead the uniqueness of a symptom, as something that returns and which has no name provided in the DSM this is one of the roles of the analyst in a mental health institution. We intend to elaborate how the attention and the management of transferential position are necessary for the child's treatment, both the transfer with responsible adults and the transfer at the institutional level, with the team which also takes care of her. To face the transferring in a broad clinical listening becomes essential to remove the reference to the individual clinic and to provide theoretical and technical information to understanding the analyst s social, collective and political role. Children s assistance in the institutional context demands from us to doubly bending toward a broadening of the analytical listening: first because the child brings with her other people who speak about her and for her; secondly because, in the institutional environment, the treatment happens in the polyphony of various knowledges. To hear these diverse voices in the clinical work is what we consider essential both for the subject to be contemplated and for the analyst s activity to reach a scope beyond the individual, understanding the child as a subject of desire formed in a close relationship with the familiar, social and political context she is immersed